Strategi Pemasaran Pengembang Perumahan Saat Pandemi Covid-19 di Kota Bandar Lampung - Antusias Nurzukhrufa; Widi Dwi Satria; Meylita Kusuma Dewi (Jurnal Maksipreneur, 2022)
Lampung is in the top ten lowest positive cases of Covid-19 in Indonesia from June 2020. Even so, the Covid-19 pandemic still affects people's interest in buying a house. Amid the pressure of the pandemic, real estate developers must be able to maintain their business continuity through a good marketing strategy. The study aims to determine the marketing strategies carried out by housing developers during the Covid-19 pandemic in Sukarame, Bandar Lampung. The research method used is qualitative with descriptive analysis techniques. Four aspects of the marketing mix theory, namely product, price, promotion, and place, are used as variables in the study. Of the four aspects, only product aspects are not affected by pandemic conditions. Developers are still using the same marketing strategies as before the pandemic. Even so, developers are still carrying out new marketing strategies through online media to get consumers during the Covid-19 pandemic.